2021
DOI: 10.1038/s41598-021-99651-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of tuberculosis in intermediate endemicity setting dominated by reactivation diseases in Hong Kong

Abstract: Summer-spring predominance of tuberculosis (TB) has been widely reported. The relative contributions of exogenous recent infection versus endogenous reactivation to such seasonality remains poorly understood. Monthly TB notifications data between 2005 and 2017 in Hong Kong involving 64,386 cases (41% aged ≥ 65; male-to-female ratio 1.74:1) were examined for the timing, amplitude, and predictability of variation of seasonality. The observed seasonal variabilities were correlated with demographics and clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Therefore, it is crucial to consider the unique immune landscapes of specific tissues when studying immune response in tuberculoma. However, it is worth noting that aging is a significant risk factor for TB, primarily due to waning immunity in the elderly [48,49]. Consequently, age-related differences in immune responses cannot be ignored in the context of TB, and future studies should explore the extent to which these differences contribute in shaping immune response in tuberculoma…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to consider the unique immune landscapes of specific tissues when studying immune response in tuberculoma. However, it is worth noting that aging is a significant risk factor for TB, primarily due to waning immunity in the elderly [48,49]. Consequently, age-related differences in immune responses cannot be ignored in the context of TB, and future studies should explore the extent to which these differences contribute in shaping immune response in tuberculoma…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses for its spring-summer surge have been proposed, including a dominant theory of the indoor congregation in wintertime or seasonal variation in meteorological factors or both [56]. A recent study in Hong Kong showed that the pattern is largely contributed to by reactivation diseases precipitated by defective immunity [57]. In comparison, the incidence of scarlet fever remained stable from 2005 to 2010; subsequently, there was a remarkable increase to nearly 5 cases per 100,000 in 2011, after which it remained steady.…”
Section: Bacterial Infectionsmentioning
confidence: 99%